2000
DOI: 10.1128/jvi.74.24.11717-11723.2000
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of Conserved Domains within the Cytoplasmic Tail of gp41 from Human Immunodeficiency Virus Type 1: Effects on Glycoprotein Incorporation and Infectivity

Abstract: The transmembrane (TM) glycoprotein gp41 of human immunodeficiency virus type 1 possesses an unusually long (ϳ150 amino acids) and highly conserved cytoplasmic region. Previous studies in which this cytoplasmic tail had been deleted partially or entirely have suggested that it is important for virus infectivity and incorporation of the gp120-gp41 glycoprotein complex into virions. To determine which regions of the conserved C-terminal domains are important for glycoprotein incorporation and infectivity, severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
64
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 38 publications
3
64
1
Order By: Relevance
“…Mutagenesis studies of CT suggest that it is involved in Env incorporation into the virus (184,260), decreased virus infectivity (251), and structural perturbations of gp120 leading to increased sensitivity to Ab-mediated neutralization (67). Other functions have been described for CT, including interaction with the viral matrix protein (48,62,72,160,260), targeting to vesicles (56,129,194), as well as interaction with other proteins (15, 102, 152, 171, 252).…”
Section: The Ctmentioning
confidence: 99%
“…Mutagenesis studies of CT suggest that it is involved in Env incorporation into the virus (184,260), decreased virus infectivity (251), and structural perturbations of gp120 leading to increased sensitivity to Ab-mediated neutralization (67). Other functions have been described for CT, including interaction with the viral matrix protein (48,62,72,160,260), targeting to vesicles (56,129,194), as well as interaction with other proteins (15, 102, 152, 171, 252).…”
Section: The Ctmentioning
confidence: 99%
“…It is also suggested that the cytoplasmic tails of envelope proteins or their interactions with M proteins are important for the efficient assembly of paramyxoviruses (6,8,9,40,41,51,52,55), rhabdoviruses (41,56), orthomyxoviruses (18,24,41), and retroviruses (17,34). Interestingly, using the Edmonston vaccine strain, Naim et al showed that the MV M protein controls the sorting of the H and F proteins (26).…”
Section: Discussionmentioning
confidence: 99%
“…A peculiar feature of gp41 is its unusually long cytoplasmic domain, typically about 150 amino acids. Truncation of the cytoplasmic domain in vitro has been associated with enhanced fusion activity but with reduced viral infectivity (19,35,36,40). In vitro passage of SIVmac in certain human cell types has been shown to select for variants with truncated cytoplasmic domains, although the nature of the resulting growth advantage remains unclear (27).…”
mentioning
confidence: 99%